Milton and the post-secular present : ethics, politics, terrorism - Mohamed, Feisal G. (Feisal Gharib), 1974- (Cultural memory in the present., 2011)
"Through a consideration of poet and polemicist John Milton, this book explores current post-secularity, an emerging category that it seeks to clarify and critique. It examines ethical and political engagement grounded in belief, with particular reference to the thought of Alain Badiou, Jacques Derrida, Jürgen Habermas, and Gayatri C. Spivak"--Publisher.